2020
DOI: 10.3390/jcm9020421
|View full text |Cite
|
Sign up to set email alerts
|

The Workflow of a New Dynamic Navigation System for the Insertion of Dental Implants in the Rehabilitation of Edentulous Jaws: Report of Two Cases

Abstract: Background: This case series describes the surgical workflow during maxillary full-arch rehabilitations in two patients through the All-on-4 concept (standard and hybrid) assisted by DTX Studio Implant Software planning and X-Guide Navigation. Results: The X-Guide Navigation enabled the drills and implants to be positioned and oriented precisely, allowing the implants to be positioned favorably under the surgical and prosthetic points of view through the avoidance of damage to the maxillary sinus and nasal cav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Lopes et al described a case of one ZI placement where the presence of three fixtures inserted in a previous rehabilitation allowed the operator to anchor a markers plate directly to the maxilla. The authors concluded that a simpler fiducial markers protocol could make the surgery faster and less complicated, considering that the screws insertion is time consuming and could condition the implant positioning [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lopes et al described a case of one ZI placement where the presence of three fixtures inserted in a previous rehabilitation allowed the operator to anchor a markers plate directly to the maxilla. The authors concluded that a simpler fiducial markers protocol could make the surgery faster and less complicated, considering that the screws insertion is time consuming and could condition the implant positioning [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second point conditions the tracking of the handle instruments in relation to the patient position detected by a camera. The evolution from an invasive cranial anchorage used in major surgeries [ 18 ] to more manageable intra-orally connected patient reference tool [ 10 , 19 , 20 ] made the DN supported implantology less invasive and more ergonomic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no need for a special drill kit, reference markers can be fixed to every drill set. This technology allows guidance even when the mouth opening is limited (Stefanelli et al, 2019;Guzmán et al, 2019;Lopes et al, 2020).…”
Section: Dynamic Navigationmentioning
confidence: 99%